The Concept Of Soul Education In Kimiya As-Sa’adah : Al-Ghazali’s Solution To The Burnout Generation And The Emptyness Of Life - Dedi Hariadi; Indah Rahayu; Labibah Sayaka Ilma; Kiki Anita Rahmawati; Muhammad Fahmi (MUADDIB Jurnal Kependidikan dan Keislaman, 2025)
This research aims to examine the concept of soul education in Kimiya as-Sa'adah by Imam Al-Ghazali and its relevance to the phenomenon of burnout and emptiness of life in the modern generation. This study uses a descriptive qualitative approach with a type of library research through analysis of primary and secondary texts. The results of the study show that soul education in Kimiya as-Sa'adah focuses on the purification of the soul, the control of passions, and the achievement of true happiness through the integration of knowledge, charity, and spiritual awareness. This concept is not only normative but also has a practical dimension in shaping character and mental health. In the contemporary context, Al-Ghazali's teachings have proven relevant in responding to burnout and emptiness in life, by offering solutions based on spiritual values and inner balance. Thus, Kimiya as-Sa'adah makes an important contribution to the development of soul education that is able to answer existential crises in the modern era.